Community development : a critical approach - Ledwith, Margaret; British Association of Social Workers; BASW, the College of Social Work. (Bristol, UK ; Portland, OR : Policy Press, 2011)
"Community development finds itself in times of unprecedented political, social and economic change, locally and globally, at the same time as divisions between poverty and privilege widen. Building practical approaches to theory and theoretical approaches to practice, this updated and expanded second edition of a bestselling text develops critiques of the changing context and identifies challenges faced by community development both at community level and as a collective force for a more just, equal and sustainable future. Featuring a range of different models of community development and illustrative stories from practitioners in the field, the new edition will be essential reading for practitioners, students and educators involved in community development, youth and community work, social work, health and education."--Publisher's website.
Opening thoughts: unprecedented political times -- Why empower? -- The story of a community -- Doing community development -- Organising in the community -- Collective action for change -- The power of ideas -- Critiques of Freire and Gramsci -- Towards a Freirean-feminist-anti-racist pedagogy -- Organising for social transformation.
"BASW, the College of Social Work."
Includes bibliographical references (p. 203-218) and index.
Keywords: Community development